PENERAPAN MOTODE DRILL UNTUK MENINGKATKAN KETERAMPILAN MEMBUAT BENDA KONSTRUKSI SISWA KELAS IV SD NEGERI 145 PEKANBARU - Helmi Yanti; Zariul Antosa; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Problems in this study is the low of value the skills SBK for fourth grade students at SDN 145 Pekanbaru. For that we need to be improved in order to improve student’s skills. The efforts to repair by apply the drill method. This research is classroom action research. This research was conducted on fourth grade students at SDN 145 Pekanbaru academic year 2013/2014. Time of the research was conducted on 14 April 2014 until 29 Mei 2014. Subject of the research is fourth grade students at SDN 145 Pekanbaru which contains of 17 men and 19 women. Data collection techniques were used that observation techniques and training techniques. Data analysis technique used is the activities of teachers and students. From the value of the process and final value of skill to the make construction objects. The result showed that the average score of students was 59.31, has an increased on first cycle to 67.85. On the second cycle, the average score was 77.50, has an increased from basic score. From the explanation above shows that the application of the drill method can increase the skill of creating object construction on fourth grade students at SDN 145 Pekanbaru.Key Word : Drill Method, Skills Make Construction Objects